Effects of sprint and change-of-direction training with or without the racket in young tennis players - Fernandez-Fernandez, J.; Vidal, E. B.; Nakamura, F. Y.; Santos-Rosa, F. J.; Granacher, U.; Sanz-Rivas, D. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To examine the effects of sprint and change-of-direction (CoD) training, with and without the racket, on performance-related qualities of young tennis players.